2003
DOI: 10.1179/003258903225005312
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of Fe-3Mn-0·6/0·7C steels sinteredin semiclosed containers in dry hydrogen, nitrogen and mixtures thereof

Abstract: 426-464 MPa, tensile strengths R m were 724-780 MPa and strains to failure were 1•6-2•0% after sintering at Dr A. Cias, Mr K. Pilch, Mrs H. Cias and Mr 1250°C. The 1120°C sintering temperature resulted in M. Sulowski are with the Academy of Mining and 10-15% lower strength values. The microstructures, Metallurgy, AGH, Al. Mickiewicza 30, 30-059 Krakow, signi cantly devoid of oxide networks, comprised

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 1 publication
2
35
0
Order By: Relevance
“…Following the thermodynamics, simple iron oxide can be reduced by H 2 at temperature lower than 500°C. More stable Cr and Mn oxides, and their spinells, require higher temperature and another reducing agent -carbon, which is creating during carbothermal reduction [11,26]. As Hryha et al reported [24,25], the simple iron oxide transforms during sintering to more stable Cr-Mn-Si complex oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the thermodynamics, simple iron oxide can be reduced by H 2 at temperature lower than 500°C. More stable Cr and Mn oxides, and their spinells, require higher temperature and another reducing agent -carbon, which is creating during carbothermal reduction [11,26]. As Hryha et al reported [24,25], the simple iron oxide transforms during sintering to more stable Cr-Mn-Si complex oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the high strength sintered steels are alloyed with Ni, Cu and Mo. This expensive and price instable alloying elements led to the attempt to use Cr and Mn in alloying sintered steels for more than fifty years [1][2][3][4][5][6][7][8][9][10][11][12][13]. The easiest way was to use admixed different powder carriers of Cr and Mn, such as ferroalloys, carbides, and master alloys, such as MCM, MVM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The main obstacle for industrial application of admixed manganese PM steels is high brittleness of sintered components. Several hypotheses have been proposed, connected with brittleness caused by microstructure heterogeneity, size of manganese carrier particles, their residue and their oxidation (Dudrova et al, 2004;Dudrova et al, 2005;Danninger et al, 2005;Cias et al, 2003).…”
Section: Brittleness Of Admixed Manganese Containing Pm Steelsmentioning
confidence: 99%
“…To avoid the formation of oxide networks, Cias (Cias et al, 2003) proposed a method employing a semiclosed container to create an active ''microclimate'' around and within the Fe-Mn-C compacts. Another alternative is sintering in a hydrogen atmosphere with low enough dew point dictated by the Ellingham-Richardson diagram.…”
Section: Oxidation Of Manganese Vapourmentioning
confidence: 99%
“…Salak proposed in [10] that part of the Mn vapour can be oxidised by atmospheric oxygen, thereby removing oxygen from the atmosphere and reducing its partial pressure, which contributes to a reduction in the dew point and facilitates the sintering of low-alloy steel. As proposed by Cias [12], at temperatures above 920 1C, sublimated Mn can react with water vapour in the sintering atmosphere, producing H 2 , according to the reaction described by Eq. (2), which increases the reducing character of the atmosphere, as described by Eq.…”
Section: Introductionmentioning
confidence: 99%